Kajian Atas Pemikiran Pembaharuan Hukum Islam Abdullah Ahmad An-Na'im - nisa', zulia; laili, afrohatul; sururi, endri miftahus (LPPM UNU BLITAR, 2023)
The development of thought in the Islamic world that is emerging today is very diverse in politics, economics, feminism, and so on. This idea emerged in Africa, India and Sudan. Apart from these areas, Islamic thought and studies have also developed widely in Europe and America. The term sharia reform that An-Na'im uses as his idea goes beyond Muslim fundamentalism and secularism in responding to contemporary discourse, including justice, democracy, human freedom as individuals and their obligations towards the environment. Is it true that Islam has been able to answer all contemporary problems, is it true that social problems have answers only outside Islam? Shouldn't Islam be a modern ideology that remains alive? This research uses normative research because the research uses library materials as the main data for analyzing cases. This research specifically examines the study of Islamic law reform ideas by Abdullah Ahmad An-Na'im. An-Naim offers a new alternative methodology in uncovering Islamic views on Human Rights. His main concern is Islamic law with its relationship to modern international issues such as human rights, modern constitutionalism and modern criminal law. According to him, Islamic law currently requires total deconstruction reform.